Continent bladder stoma - Dunglison, Nigel Timothy; Gardiner, Robert Alexander (World journal of urology, 2003)
The formation of an aesthetically desirable urinary diversion through a continent bladder stoma requires a long-term commitment by both patient and urologist to monitoring patient progress and addressing problems, both urological and otherwise, which arise over time. In this manuscript, issues relating to physical aspects of surgical management are discussed. These include the nature of and site of the stoma and its catheterizing track, the continence mechanism, provision of a low-pressure storage system of adequate capacity and management of the bladder neck/urethra when incompetent. It is imperative that careful patient selection is practised at the outset when such surgery is contemplated, otherwise a satisfactory outcome is unlikely to ensue irrespective of the procedural skills employed operatively.